#TITLE_ALTERNATIVE# - DARMO YUWONO (NIM : 25110002); pembimbing: Prof.Ir. Hasanuddin Z. Abidin, M.Sc.; Ph.D Muh, BAMBANG
Land subsidence has been a common problem which is often found in big cities including Semarang. Geological settings and human activities are suspected to be the triggers of land subsidence. The characteristics of the land subsidence vary spatially and temporally due to different factors. The characteristics of the pattern of land subsidence need to be mapped for the purposes of planning and structuring the city as well as taking appropriate actions in anticipating and mitigating the impact. These characteristics can be determined by combining the land subsidence measurements done with various methods such as basic trait, GPS, direct measurement and InSAR. Geospatial analysis for identifying the causes of land subsidence is based on the spatial relationship between the characteristics of the land subsidence and both the factors contributing to the subsidence and the condition of the land cover. Land subsidence that occurred in Semarang had a rate that varied between 0 - 13 cm / year with an increasing trend towards the north east (northeast) of Semarang. The areas which had a high rate of land subsidence between 9 -13 cm / year included PRPP, Tanjungmas, Terboyo and Kaligawe. This research shows that the pattern of land subsidence is identical to the compresibility index and the decline rate of ground water level. Areas with high land subsidence rate had high decline rate of ground water level and high compressibility index; such cases were found at PRPP, Terboyo and Penggaron. Impacts of land subsidence included damage to buildings, infrastructure and environment and were spread evenly in areas with high land subsidence rate such as Tambakrejo, Kemijen, Tanjungmas, Bandarharjo and Trimulyo. Land subsidence might also cause the extension of tidal inundation. Prediction of inundation area in year 2040 with the influence of land subsidence reaches 8094,71 Ha, which increases 100% compared to prediction of inundation area without the influence of land subsidence in 3739,10 Ha.